IMPLEMENTASI KURIKULUM 2013 DINTINJAU DARI KOMPETENSI PEDAGOGIK GURU SMA NEGERI DI KECAMATAN ILIR BARAT 1 PALEMBANG - Binar Azwar Anas Harfian (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
This study aims to find out the implementation of the Curriculum 2013 in terms of pedagogic competence of biology teachers in SMA Negeri Kecamatan Ilir Barat 1 Palembang. This was a survey study and the data were collected from principals, teachers of biology class XI, and grade XI students of the science program of senior high schools in Ilir Barat 1 Palembang District, that have implemented Curriculum 2013, in the academic year of 2014/2015. The research instruments were questionnaires, interviews, observation guides, and documentation. The data were analyzed by using the qualitative descriptive analysis. The results of the analysis are as follows. Biology teachers’ readiness level to implement Curriculum 2013 in terms of pedagogic competence in state senior high schools in Ilir Barat 1 PalembangDistrict is that one teacher is in a very prepared category with a percentage of 83% and three teachers are in the ready category each having a percentage of 81%, 71%, and 71% subsequently.